This is simple question but I kept getting -13 when the asnwer should be -7. I can't figure out what I am doing wrong.
I probably did it wrong, please correct! thanks so much!
5 = 3-k/4+6
5 = 3-k/-2
-10 = 3-k
-13 = k?
hmmm
I'm trying to interpret the problem. I'm going to assume that it is
First, subtract 6 from both sides to get
Now multiply both sides by 4 to get .
Solving for , we see that .
If the answer really is , then I think the problem would have to be
Does this make sense? If you have further comments or questions, please post back!